Los consumidores cara a cara con los mensajes : El efecto cereal y el sexo como promesa de venta (2009)
The following article is a reflection in which the expression Cereal Effect is proposed by the author to characterize those marketing campaigns that succeed in affecting consumer`sdecisions throughout whole generations by offering gifts, presents and/or toys to children to attract their attention and assuring their loyalty in the long run, just as sexist iconographytargeted towards adult population takes advantage of affective demands to turn to the promise of sex as the main strategy. The article then invites schools and universities to educatetheir students in communication, advertisement and media management with responsibility so the messages conveyed are creative, fun and educative, replacing sexist iconography with new more-emotional schemes to reach target audiences